FAMILY-BASED SOCIALIZATION OF THE UTILIZATION OF FAMILY MEDICINAL PLANTS TO PRESERVE COMMUNITY HEALTH IN TUNJANG UTARA HAMLET, PAOKMOTONG - Baiq Risma Fatmayanti; Leny Ramadhan; Ramdhani Qurro’tun Adawiyah; Rindang Wulan Sari; Nurhidayati; Rizka Buana; Didik Daniyantara (Universitas Airlangga, 2026)
Introduction: Medicinal plants as an alternative herbal medicine source with many health benefits. However, the Tunjang Utara hamlet community's knowledge and skills in processing family medicinal plants as traditional medicine are still lacking. This study aims to conduct family-based socialization and to evaluate its effectiveness in improving community knowledge of the utilization of family medicinal plants for health maintenance. Methods: Current community services include three initial stages, which are pre-activities (observation and preparation); main activities (socialization by door-to-door method and herbal medicine plantation); and program evaluation. The target population was the community in Paokmotong village, with 47 participants as the sample. Data were analyzed using descriptive statistics, the Shapiro–Wilk test, and a paired sample t-test to evaluate the effectiveness of the socialization program. The community in Tunjang Utara Hamlet is expected to actively utilize traditional medicinal plants and share this knowledge with other communities after the program. Results: At the observation stages, we found that Tunjang Utara’s communities did not know the benefit of family medicinal plants other than as additional cooking ingredients. The socialization was successfully carried out to give the information about the benefits of family medicinal plants. The results showed a significant increase in participants’ knowledge after the socialization program, with the mean score rising from 55.32 ± 8.14 (pretest) to 80.47 ± 7.26 (posttest), indicating a statistically significant difference (p < 0.001). Moreover, 10 medicinal plants were successfully planted at the Pokmotong village office. Conclusion: The socialization program effectively improved community knowledge of the use of family medicinal plants, as indicated by a significant increase in posttest scores relative to pretest scores. However, we suggest that the Paokmotong village government create a follow-up program to socialize the use of family medicinal plants in other hamlets in a sustainable manner. KEYWORDS community service; family medicinal plants; health; socialization; Tunjang Utara hamlet